Flexible reamer use to overcome entry point errors in proximal femoral nail application in severe obese intertrochanteric fracture patients - Levent Horoz; Ali Ihsan Kilic; Cihan Kircil; Mehmet Fevzi Cakmak (BMC Musculoskeletal Disorders)
Abstract Introduction Proximal femoral nailing (PFN) offers biomechanical benefits for intertrochanteric fractures but can lead to higher complication rates from poor reduction and technique errors, particularly in obese patients. Incorrect entry points may cause reduction loss, iatrogenic fractures, and misplaced lag screws. The study aims to investigate the effect of using an oriented flexible reamer instead of a rigid reamer on clinical and radiological results to obtain a medial entry point and better positioning of the nail in the intramedullary area in obese intertrochanteric fracture patients. Materials and methods A retrospective analysis was conducted on patients aged 65 years and older who underwent PFN treatment between March 2020 and June 2022 at a single institution, with at least 1-year postoperative follow-up. Patients were divided into two groups: those applied with a flexible reamer and a rigid reamer. Parameters analyzed from postoperative radiographs included tip-apex distance (TAD), calcar-referenced tip-apex distance (CalTAD), reduction quality, femoral neck-shaft angle, and lag screw placement. Complication rates and types were recorded for each group. Result The analysis included 91 patients, with 45 treated using a flexible reamer and 46 treated using a rigid reamer. There was no statistical difference between the two groups regarding age, gender, BMI, and AO class distributions of the patients (p > 0.05). The Femur neck shaft angle was significantly higher in the flexible reamer group (p < 0.001). As a result of the reduction types analysis, medial type reduction was significantly higher in the group where the flexible reamer was applied (p < 0.001). The CalTAD was shorter in the Flexible reamer group (p = 0.005). Complications and the need for reoperation were statistically significantly higher in the rigid reamer group (p < 0.048). Conclusion The oriented flexible reamer reduces application-related errors in patients undergoing proximal femoral nail (PFN) treatment due to intertrochanteric fracture. The oriented flexible reamer technique allows a more medial entry point. Oriented flexible reamer creates enough space on both fracture sides at the level of intertrochanteric fracture to avoid nail pass-related complications. Level of evidence Level III, Case-control study.